The use of postprocessing and its impact on rendering performance in the Unreal Engine 4 - Puławski, Eryk; Tokarski, Marcin (Journal of Computer Sciences Institute, 2019)
t. Today’s 3D graphics are hard to imagine without the effects known to us from film productions or high-budget video games. However, the use of such embellishments is associated with an increased demand for computing power. In order to meet the expectations of developers and consumers on the 3D applications market, tools for their creation in the form of comprehensive engines were created. One of these solutions is the Unreal Engine. The following article examines the impact on the efficiency of these effects - postprocesses. For this purpose, a test stage and two test scenarios were prepared.